Performance of white oat cultivars in response to nitrogen fertilization and trinexapac-ethyl - Bazzo, José Henrique Bizzarri; Riede, Carlos Roberto; Arruda, Klever Márcio Antunes; Cardoso, Carolina Pereira [UNESP]; Franzoni, Isabela; De Batista Fonseca, Inês Cristina; Zucareli, Claudemir (Universidade Estadual de Londrina, 2019)
The application of N at the appropriate time and dose can increase oat crop efficiency by increasing grain yield through changes in production components. High doses of N, depending on the genotype and the environment, can result in plant lodging, which can be addressed with the use of growth retardants. The aim of this study was to evaluate the yield components, lodging, and productivity of white oat cultivars cultivated at two growing locations under different N levels with trinexapac-ethyl growth retardant. Two assays (with and without the application of the growth retardant agent) were used in the experiments, which were set up in the region of Londrina and Mauá da Serra, Parana State, Brazil, in a randomized block design with split plots and four replications. The plots consisted of four white oat cultivars (IPR Afrodite, IPR Artemis, URS Corona, and URS Guria) and the subplots of four doses of N (0, 30, 60, and 90 kg ha-1). Plant height, number of panicles per unit area, number of grains per panicle, thousand grain weight, lodging of plants, and grain yield were evaluated. The growth retardant decreased plant height and lodging at the both growing locations. Furthermore, the growth retardant in combination with N topdressing increased the number of panicles per unit area. Thus, the increase in grain yield with the application of a growth retardant was dependent on the characteristics of the plant growth environment. The response of genotypes to N fertilization was also dependent on the soil and climatic characteristics of the environment.
Keywords: Avena sativa L; Growth regulator; Lodging; Nitrogen; Productivity